The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/ejlt.201300339
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing wild and farm‐raised freshwater fish through fatty acid composition: Application of statistical tools

Abstract: Brazil stands out on the world stage as having the greatest variety of freshwater fish and great aquaculture potential due to a number of factors favorable to fish production. In order to classify fish according to their fatty acid composition and origin (wild vs. farm-raised), a survey of data from native Brazilian freshwater fish was conducted. These data were subjected to statistical analyses (principal component analysis [PCA], cluster analysis, as well as ordination by nonmetric multidimensional scaling [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
(17 reference statements)
2
0
0
Order By: Relevance
“…L. friderici showed the highest variation in this ratio, which varied from 3.65 in the drought period to 3.05 in the flood period. Results for n-6/n-3 ratio were in accordance with those values reported by Carbonera et al [39] for Brazilian wild freshwater fish. Other studies have also shown a season-dependent n-6/n-3 ratio as a result of the variation in fatty acids composition [16,27,28].…”
Section: Fatty Acids Compositionsupporting
confidence: 92%
“…L. friderici showed the highest variation in this ratio, which varied from 3.65 in the drought period to 3.05 in the flood period. Results for n-6/n-3 ratio were in accordance with those values reported by Carbonera et al [39] for Brazilian wild freshwater fish. Other studies have also shown a season-dependent n-6/n-3 ratio as a result of the variation in fatty acids composition [16,27,28].…”
Section: Fatty Acids Compositionsupporting
confidence: 92%
“…Values varied from 0.88 to 0.97 for B. cephalus and 0.91 to 0.98 for B. microlepis. These results were higher than those reported by Moreira et al (2001) and Almeida and Franco (2007) in the same species; however, they were in accordance with values reported in Brazilian wild freshwater fish by Carbonera et al (2014).…”
Section: Fatty Acids Compositionsupporting
confidence: 89%